Analisis Penerapan Otago Exercise pada Lansia Risiko Jatuh - Warijan Warijan; Ajeng Titah Normawati; Cipto Cipto (Jurnal Kesehatan, 2022)
Background: Aging is an economic and social challenge in the modern era that often occurs at this stage is the incidence of falling which is one of the geriatric giants because it often results in injury. One of the efforts to prevent falls is through the application of Otago exercises. Purpose: This study describes the analysis of nursing care with the application of Otago Exercise in the elderly at risk of falling used a qualitative case study approach. Results: This study involved three elderly with a risk of falling as samples, who are assessed using the Berg Balance Score instrument. The elderly were given the intervention of applying Otago exercise as much as six exercises for three consecutive weeks. The results of the implementation describe the outcome criteria in the form of increasing the ability to walk, move places, and maintain a stable standing position and sitting position. Evaluation of the berg balance score measurement showed that their experienced an increase in balance score but were still in the same fall risk category. Conclusion: Based on this study, elderly can apply Otago exercise on an ongoing basis with their families to maintain the quality of their health, especially preventing falls.